SISTEM INFORMASI MONITORING INVENTORI BARANG PADA BALAI RISET STANDARDISASI INDUSTRI BANDAR LAMPUNG - Ochi Marshella Febriani; Arie Setya Putra (IIB Darmajaya, 2013)
Industry Research and Standardization Bandar Lampung or shortened by Industry Baristand a Government agency under the Ministry of Industry which was established in 1975, is engaged in the research , mastery of technology , testing for food products , agro- industry, as well as technical training in order to support the growth of industrial sector in Lampung province. However, there are still many obstacles that arise and the absence of inventory monitoring system special items resulting in invalid data items due to lack of information which supports the above data processing. Center for Standardization and Industrial Research of Bandar Lampung need to do a good evaluation of the data by monitoring information system to control the inventory items borrowing and returning items through inventory monitoring. Monitoring information system of goods inventory will be made ​​of a system development. Keywords: Monitoring inventory, Information Systems